Pengaruh Kompetensi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT Advik Indonesia Bekasi - Neny Anggreany; Hartono (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to determine the extent to which competence and work discipline influence employeeperformance at PT Advik Indonesia Bekasi. This study uses a quantitative approach. The respondentsin this study are employees of PT Advik Indonesia. The number of respondents used in this study is 90people. The results of this study indicate that Competence (X1) influences Employee Performance (Y)at PT Advik Indonesia by 51.5%. Work Discipline (X2) influences Employee Performance (Y) at PTAdvik Indonesia by 57.8%. Competence (X1) and Work Discipline (X2) simultaneously influenceemployee performance (Y) at PT Advik Indonesia by 0.618 or 61.8%.Keywords: Freight Forwarder Performance, Service Quality, Effectiveness of The ExportProcess, International Trade